2017
DOI: 10.17148/iarjset.2017.4322
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Soil Media Characteristics on Stormwater Biofiltration System Performance

Abstract: Stormwater bioinfiltration systems can be effective options for the treatment and disposal of stormwater runoff from urban areas. However, the performance of these systems and other infiltration devices can be affected by factors such as texture, structure and degree of compaction of the treatment media. This study provides insights on media characteristics of a poorly operating biofilter facility located in Tuscaloosa, AL, along with supporting laboratory investigations. Double ring infiltrometer tests and so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Sileshi (2013) conducted a large number of laboratory column tests examining treatment flow rates for various mixtures of stormwater biofilter media as part of his dissertation research. These tests and data are described in his dissertation, available here, and in Sileshi et al (2014Sileshi et al ( , 2017Sileshi et al ( , 2018. Sileshi (2013) found that the biofilter media treatment flow rates were mostly affected by the median mixture particle size (D50) and the uniformity coefficient (D60/D10) of the media mixture, and the amount of organic matter.…”
Section: Treatment Flow Rates For Biofilter Media Components and Mixturesmentioning
confidence: 97%
“…Sileshi (2013) conducted a large number of laboratory column tests examining treatment flow rates for various mixtures of stormwater biofilter media as part of his dissertation research. These tests and data are described in his dissertation, available here, and in Sileshi et al (2014Sileshi et al ( , 2017Sileshi et al ( , 2018. Sileshi (2013) found that the biofilter media treatment flow rates were mostly affected by the median mixture particle size (D50) and the uniformity coefficient (D60/D10) of the media mixture, and the amount of organic matter.…”
Section: Treatment Flow Rates For Biofilter Media Components and Mixturesmentioning
confidence: 97%